Informal employment relationships and the labor market: Is there segmentation in Ukraine? - Hartmut Lehmann; Norberto Pignatti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2018)
One of the most important factors that determine individuals' quality of life and wellbeing is their position in the labor market and the type of jobs that they hold. When workers are rationed out of the formal segment of the labor market against their will, i.e., the labor market is segmented, their quality of life is limited, and their wellbeing is reduced. When they can freely choose between a formal or informal employment relationship, i.e., the labor market is integrated, their wellbeing can reach high levels even in the presence of informal employment. We, therefore, test whether the Ukrainian labor market is segmented along the formal-informal divide, slicing the data by gender and age. The analysis that we perform consist in the analysis of short-term and medium-term transitions between five employment states, unemployment and inactivity. We also analyze wage gaps of mean hourly earnings and across the entire hourly earnings distribution, controlling for time-invariant unobserved heterogeneity. According to our results segmentation is present for dependent employees: for a large part of informal employees informal employment is used as a waiting stage to enter formal salaried employment and is not voluntarily chosen. As far as self-employment is concerned the evidence is mixed regarding in the Ukrainian labor market. This heterogeneity in outcomes implies that not all informal work is associated with a low quality of life and reduced wellbeing in post-transition economies.
Keywords: J31; J40; P23; 330; Informal Employment; Labor Market Segmentation; Transition Economies; Ukraine